Neratinib and the Role of Anti‐HER2 Therapy in Salivary Duct Carcinoma - Martina Napolitano; Lucia Trudu; Enrica Martinelli; Chiara Santini; Massimo Dominici; Federica Bertolini (Cancer Reports)
ABSTRACT Backgroud Salivary duct carcinoma (SDC) is a rare and aggressive malignancy with a generally dismal prognosis and no standard of care established, despite a known association with epidermal growth factor receptor 2 (HER2) and androgen receptor (AR) over‐expression. Case We report the case of a 64‐year‐old female with extra‐ and intracranial metastases of SDC with evidence of AR and HER2 overexpression. After progression on first line chemotherapy, was administered neratinib, a pan‐Erb2 receptor tyrosine kinase inhibitor. Even with central nervous system involvement at diagnosis, a durable clinical response was obtained with a PFS of 11 months and no significant toxicities to manage. Best response observed during tratment was partial response. Conclusions This case confirms the potential efficacy of neratinib in HER2‐positive SDC and underlines the need to define the best therapeutic sequence and potential biomarkers for these rare patients.